Desain dan Analisa Pembakaran Kompor Briket Biomassa - Ramadhan, Ramadhan; Kadir, Kadir; Hasanudin, La (Teknik Mesin Universitas Halu Oleo, 2020)
The furnace is a device used to convert potential energy into heat energy. Furnace for the community is one of the important tools for cooking. Combustion is the reaction of a substance with oxygen (O2 ). Combustion is one of the most widely used biomass energy conversions because it produces direct thermal energy. The purpose of this research is to analyze the number of holes and analyze the comparison of burning briquette stoves with kerosene stoves. The data collection method is carried out by direct observation of the community and collecting references from related books and journals. Analysis conducted on the number of holes in the briquette stove (21, 33 and 43) shows the most effective results in the use of briquette stoves are briquette stoves which have 43 holes. The time to heat the water is 15 minutes with the same amount of water and fuel volume, the water volume is 500 ml and 600 grams of fuel and the final temperature is 100 oC. The heating time of kerosene stove is 12 minutes and the heating time of briquette stove is 15 minutes.Keywords: Briquette stove, hole variation, design, combustion, efficiency